GUIDELINES FOR MONITORING WOMEN WITH COAGULATION DISORDERS - Savović, Miodrag (Acta medicae Medianae, 2024)
Irrespective of the progress in the recognition and treatment of women who suffer from bleeding disorders, modern medical science has yet to adjust the diagnosis, therapy and care to their needs. An increasing number of women are being diagnosed with the mentioned disorders. Some who consult a gynaecologist owing to heavy menstrual bleeding actually have a coagulation disorder. Failure to recognise this disorder is widespread. Heavy menstrual bleeding is a condition that women with such disorders experience from the onset of the reproductive period. It affects their quality of life. What is more, they face the problem of accepting the potential risks of transmitting the disease to their child. Timely recognition and registration of these patients are essential. It is important to talk with and consult healthcare professionals, as well as to prescribe adequate therapy that enables physicians to cope with the various needs of women during the reproductive period.
Keywords: menarche, coagulopathies, abnormal uterine bleeding